2019
DOI: 10.1371/journal.pone.0227071
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pathogen identification and antimicrobial susceptibility testing in in vitro endophthalmitis with matrix assisted laser desorption-ionization Time-of-Flight Mass Spectrometry and VITEK 2 without prior culture

Abstract: PurposePrompt clinical diagnosis and initiation of treatment are critical in the management of infectious endophthalmitis. Current methods used to identify causative agents of infectious endophthalmitis are mostly inefficient, owing to suboptimal sensitivity, length, and cost. Matrix Assisted Laser Desorption-Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) can be used to rapidly identity pathogens without a need for culture. Similarly, automated antimicrobial susceptibility test systems (AST, VITEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
(47 reference statements)
0
9
0
2
Order By: Relevance
“…Staphylococcus hominis, Vibrio alginolyticus, and Bacillus licheniformis collected from marine environments were used in this study. Single colonies of each pure culture from LB agar plates were inoculated into 10 mL LB, followed by cultivation overnight at 37 °C in a shaker incubator (Coconnier et al, 1993). After 12 h of incubation, the cells were harvested by centrifuging at 12,000 rpm for 2 min and were then resuspended in sterile physiological saline twice.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus hominis, Vibrio alginolyticus, and Bacillus licheniformis collected from marine environments were used in this study. Single colonies of each pure culture from LB agar plates were inoculated into 10 mL LB, followed by cultivation overnight at 37 °C in a shaker incubator (Coconnier et al, 1993). After 12 h of incubation, the cells were harvested by centrifuging at 12,000 rpm for 2 min and were then resuspended in sterile physiological saline twice.…”
Section: Sample Preparationmentioning
confidence: 99%
“…However, studies on identification methods for marine pathogens are very rare (Cantrell et al, 2020). The identification of pathogens by traditional methods is mainly based on the morphological and physiological characteristics and biochemical reactions of colonies (Chun et al, 2019). Such methods are not only time consuming and laborious but also tedious and complex, and their effectiveness in isolating similar pathogens is not high (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian eye has the feature of acting as its own culture bottle with, albeit limited, nutritional media, and can serve as a reservoir for pathogenic growth. Stemming from this principle, the potential utility of MALDI-TOF MS for direct analysis of infectious endophthalmitis samples, was previously explored in a proof-of-concept study by the authors of this review [ 49 ]. In an in vitro model of bacterial endophthalmitis, vitreous humor aspirated from freshly enucleated porcine eyes was inoculated and incubated at 37 °C with different inocula of S. aureus , and minimally processed with centrifugation to form bacterial pellets for direct analysis with matrix solution α-cyano-4-hydroxycinnamic acid.…”
Section: Maldi-tof Ms: Using Proteomic Fingerprints To Find the Culpr...mentioning
confidence: 99%
“…VITEK 2 AST has been shown to have a high degree of agreement with standard methods for determining the minimum inhibitory concentration (MIC) of antibiotics, with a gain-of-time of hours to days, and high reproducibility [ 62 , 63 ]. The authors of this review demonstrated that VITEK 2 can be used to directly analyze vitreous humor samples from in vitro models of S. aureus endophthalmitis without prior culture, with up to 94.4% concordance with conventional methods [ 49 ]. Time to result attainment was 8–9.25 h with direct analysis with VITEK 2, in contrast to the multiple days needed via conventional methods [ 37 , 38 ].…”
Section: Maldi-tof Ms: Using Proteomic Fingerprints To Find the Culpr...mentioning
confidence: 99%
“…Despite recent advances in the science and technology for the identification of pathogens using polymerase chain reaction (PCR) [ 39 , 40 ] and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry [ 41 , 42 ], new antibiotics, and minimally invasive vitrectomy, bacterial endophthalmitis remains a severe intraocular infection that causes a high risk of vision loss. Recently, a large cohort study in Japanese patients with postoperative endophthalmitis after cataract surgery showed that the incidence of endophthalmitis was 0.025% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%